Traumatic counseling: An alternative problem solving post traumatic stress disorder for natural disaster victims in Indonesia - Wangsanata, Susana Aditiya; Jamalullael, Jaiz; Khakim, Lukman; Maulidawati, Maulidawati; Andres Sanjaya, Lari (Jurnal Ilmu Dakwah, 2024)
Purpose - The purpose of this study is to explain traumatic counseling services as an alternative problem solving for Post Traumatic Stress Disorder (PTSD) in Natural Disaster Victims in Indonesia. Method - This research method is a literature explaining the form of traumatic counseling services and psychological injuries for victims of natural disasters. Data sources are collected from previous research results, valid official government website sources and relevant to the focus of this research problem. Data analysis uses content analysis that focuses on text, images and audio in the context of traumatic counseling and PTSD for victims of natural disasters. Result  -  The results of this study indicate that traumatic counseling is suitable for treating PTSD for victims of natural disasters in Indonesia. The psychological condition of victims of natural disasters has psychological wounds from events and experiences that leave a mark so that it has an impact on the psychological health of the victims. This impact affects the sustainability of the victim's life, so that healing psychological trauma with counseling services. The approach in counseling services can use two models, namely SEFT and CBT. The two models are suitable for reducing PTSD in victims of natural disasters. Implication – The findings of this study are that there is a relevant meeting point between traumatic counseling and psychological injuries of natural disaster victims with PTSD disorders. With traumatic counseling, it is hoped that natural disaster victims will be able to determine the right direction to overcome PTSD of natural disaster victims in Indonesia in the future. Originality/Value - This study is unique because it is able to position traumatic counseling as an appropriate preventive service for natural disaster victims in Indonesia. *** Tujuan - Tujuan dari penelitian ini adalah untuk menjelaskan layanan konseling traumatik sebagai alternatif pemecahan masalah Post Traumatic Stress Disorder (PTSD) pada Korban Bencana Alam di Indonesia. Metode - Metode penelitian ini adalah literatur yang menjelaskan bentuk layanan konseling traumatik dan luka psikologis bagi korban bencana alam. Sumber data dikumpulkan dari hasil penelitian terdahulu, sumber website resmi pemerintah yang valid dan relevan dengan fokus masalah penelitian ini. Analisis data menggunakan analisis isi yang berfokus pada teks, gambar dan audio dalam konteks konseling traumatik dan PTSD bagi korban bencana alam. Hasil - Hasil dari penelitian ini menunjukkan bahwa konseling traumatik cocok digunakan untuk menangani PTSD bagi korban bencana alam di Indonesia. Kondisi psikologis korban bencana alam memiliki luka psikologis dari kejadian dan pengalaman yang membekas sehingga berdampak pada kesehatan psikologis korban. Dampak tersebut berpengaruh pada keberlangsungan hidup korban, sehingga penyembuhan trauma psikologis dengan layanan konseling. Pendekatan dalam layanan konseling dapat menggunakan dua model, yaitu SEFT dan CBT. Kedua model tersebut cocok digunakan untuk mengurangi PTSD pada korban bencana alam. Implikasi - Temuan dari penelitian ini adalah adanya titik temu yang relevan antara konseling traumatik dengan luka psikologis korban bencana alam dengan gangguan PTSD. Dengan adanya konseling traumatik, diharapkan korban bencana alam dapat menentukan arah yang tepat untuk mengatasi PTSD korban bencana alam di Indonesia di masa yang akan datang. Orisinalitas/Nilai - Penelitian ini memberikan kontribusi mengenai posisi, arah dan tujuan layanan konseling traumatik dalam mengatasi PTSD korban bencana alam di Indonesia. Penelitian ini memiliki keunikan karena mampu memposisikan konseling traumatik sebagai layanan preventif yang tepat bagi korban bencana alam di Indonesia.